Enhanced antibacterial activity through the controlled alignment of graphene oxide nanosheets - Lu, Xinglin (Proc Natl Acad Sci U S A, 2017)
The cytotoxicity of 2D graphene-based nanomaterials (GBNs) is highly important for engineered applications and environmental health. However, the isotropic orientation of GBNs, most notably graphene oxide (GO), in previous experimental studies obscured the interpretation of cytotoxic contributions of nanosheet edges. Here, we investigate the orientation-dependent interaction of GBNs with bacteria using GO composite films. To produce the films, GO nanosheets are aligned in a magnetic field, immobilized by cross-linking of the surrounding matrix, and exposed on the surface through oxidative etching. Characterization by small-angle X-ray scattering and atomic force microscopy confirms that GO nanosheets align progressively well with increasing magnetic field strength and that the alignment is effectively preserved by cross-linking. When contacted with the model bacterium Escherichia coli, GO nanosheets with vertical orientation exhibit enhanced antibacterial activity compared with random and horizontal orientations. Further characterization is performed to explain the enhanced antibacterial activity of the film with vertically aligned GO. Using phospholipid vesicles as a model system, we observe that GO nanosheets induce physical disruption of the lipid bilayer. Additionally, we find substantial GO-induced oxidation of glutathione, a model intracellular antioxidant, paired with limited generation of reactive oxygen species, suggesting that oxidation occurs through a direct electron-transfer mechanism. These physical and chemical mechanisms both require nanosheet penetration of the cell membrane, suggesting that the enhanced antibacterial activity of the film with vertically aligned GO stems from an increased density of edges with a preferential orientation for membrane disruption. The importance of nanosheet penetration for cytotoxicity has direct implications for the design of engineering surfaces using GBNs.